Blue, green and yellow carbon dots derived from pyrogenic carbon: Structure and fluorescence behaviour. (5th January 2023) - Russo, C.; Carpentieri, A.; Tregrossi, A.; Ciajolo, A.; Apicella, B.
Abstract: Fluorescence lifetimes and quantum yields featuring polycyclic aromatic hydrocarbons (PAHs) and other organics constituting pyrogenic carbon particulate matter (PM) are seldom measured. In this work, PM sampled in a fuel-rich ethylene flame was firstly separated in organic carbon (OC), soluble in dichloromethane, and refractory organic carbon (ROC), soluble in N -methyl pyrrolidinone, and then analyzed by size exclusion chromatography (SEC) coupled with online UV and fluorescence detection, and by offline fluorescence spectroscopy and mass spectrometry. It was found that three classes of differently light emitting carbon dots (CDs) could be bottom-up synthesized in the same flame system by selecting appropriately the residence time. Actually, OC presented blue fluorescence regardless the residence time, whereas ROC sampled at low and high residence time emitted fluorescence in the green (green CDs) and in the yellow (yellow CDs) region, respectively. The SEC molecular weight of all CDs presented similar trimodal distributions, centered around 300, 1000 and 10, 000 u. For the first time fluorescence lifetimes and quantum yields of pyrogenic CD fractions were measured as additional parameters useful for discriminating the fluorescent components and inferring their structural properties, with the support of mass spectrometry. The different spectroscopic features of CDs could be associated to different compositional characteristics as the polydispersity of molecular components featuring blue CDs, opposed to the oligomer-like nature of green and yellow CDs. Pyrogenic CDs showed different fluorescence emission ranges, quantum yield and lifetimes, appealing for their possible applications in the fields of imaging, electronics and sensors. Graphical abstract: Image 1